Designing English Supplementary Materials Integrated with Riau Malay Heritage for Tenth-Grade Students in Pekanbaru - Marhamah Marhamah; Cyintia Kumalasari; Ratu Ganisa Auliana; Sumardi Sumardi (STAI Hubbulwathan Duri, 2025)
English learning materials that incorporate local culture are limited, particularly those that reflect and preserve the Riau heritage. As Malay culture is deeply rooted in Islamic values, integrating these elements into language education can promote cultural transmission while enhancing student engagement. This study aims to design English learning materials that embed Riau cultural elements for tenth-grade students in Pekanbaru. This study adopts a descriptive-evaluative method within the Research and Development (RD) model proposed by Borg and Gall. The full model includes ten phases, but this research focuses specifically on the design phase (stages 2 and 3): learning objective planning and initial draft creation. Activities during this phase involved identifying and analyzing learning goals, assessing student characteristics, and developing a structured instructional plan. The subjects consisted of 40 tenth-grade students. The design process yielded English learning materials that integrate Riau heritage through culturally relevant texts and context-based exercises. The content was tailored to students' backgrounds to foster deeper comprehension, engagement, and emotional connection with the material. The materials were structured to support language acquisition while simultaneously promoting cultural preservation. Embedding local heritage into English language learning helps students develop linguistic proficiency and cultural identity simultaneously. These culturally infused materials are expected to enhance student motivation, interest, and participation by making learning more meaningful and relatable. This study provides a framework for developing localized educational content that fosters both academic and cultural growth, enabling students to share their heritage with a global audience.